Arabidopsis mutants resistant to the auxin effects of indole-3-acetonitrile are defective in the nitrilase encoded by the NIT1 gene. - Normanly, J (1997)
Indole-3-acetonitrile (IAN) is a candidate precursor of the plant growth hormone indole-3-acetic acid (IAA). We demonstrated that IAN has auxinlike effects on Arabidopsis seedlings and that exogenous IAN is converted to IAA in vivo. We isolated mutants with reduced sensitivity to IAN that remained sensitive to IAA. These mutants were recessive and fell into a single complementation group that mapped to chromosome 3, within 0.5 centimorgans of a cluster of three nitrilase-encoding genes, NIT1, NIT2, and NIT3. Each of the three mutants contained a single base change in the coding region of the NIT1 gene, and the expression pattern of NIT1 is consistent with the IAN insensitivity observed in the nit1 mutant alleles. The half-life of IAN and levels of IAA and IAN were unchanged in the nit1 mutant, confirming that Arabidopsis has other functional nitrilases. Overexpressing NIT2 in transgenic Arabidopsis caused increased sensitivity to IAN and faster turnover of exogenous IAN in vivo.